Determinant Factors for Couple Communication and Marital Stability among Adults in Assela Town, Oromia Region, Ethiopia (Global Journal of Human-Social Science, 2018)
The aim of the present study was to assess the determinant factors of couple communication and marital stability among adults in Assela Town, Oromia Region, Ethiopia. Community-based crosssectional survey research design was used. Proportionately stratified sampling along with simple random sampling technique was employed to recruit 390 respondents from 8 kebeles in Assela Town. Apart from the interview, Marital Communication Questionnaire (MCQ) and Marital Stability Questionnaire (MSQ) was employed to measure the status of marital communication and marital stability respectively. Descriptive statistics (percentage, mean and standard deviation), independent sample t-test, ANOVA, and Pearson correlation coefficient were used to analyze the data. Findings indicated that the independent sample ttest result shows that sex of respondents had statistically significant mean difference in marital communication (t (388) = 6.868, p < 0.05) and marital stability (t (388) = 3.966, p < 0.05) respectively. In this study, ANOVA result revealed that educational status (F (3,386) = 357.877, p < 0.05), length of stay in marriage (F (3,386) = 62.437, p
Keywords: couple communication; marital stability; marriage